Human Resources Readiness of Small Medium Enterprises (SMEs) for Halal Product in Indonesia - Jaenal Effendi (Global Review of Islamic Economics and Business, 2022)
The halal industry has caught the attention of the world today. The halal industry is not only in demand by Muslim countries but also by countries with non-Muslim majority populations. The implementation of the halal certification program for Small and Medium Enterprises (SMEs) also affects the process of developing SMEs' human resources in Indonesia. Increasing the capacity of human resources is needed to improve the competence, skills, innovation, and creativity of individuals in carrying out productive activities to increase domestic production. This study is expected to be able to provide an overview (steps that need to be achieved, policy strategies, and various efforts that need to be made) related to the role of government bureaucracy, academics, and business actors in optimizing the halal product guarantee system to support the halal industry in Indonesia. This study uses a combination of qualitative and quantitative data. The method used is literature study, in-depth interview, benchmark, and Analytical Networking Process (ANP). A strategic solution for SMEs in increasing the halal market segment is the need for socialization of assistance and submission of halal certification. In addition, the implementation of integrated halal product supply chain management is very necessary to ensure the quality of halal products and services.